The Experiences of Cancer Patients Undergoing Treatment at Oshakati Oncology Clinic, Oshana Region, Namibia - Mulenga, Ester; Mutanga, Elise (An Overview of Disease and Health Research Vol. 1, 2025)
Cancer is one of the global health problems. People living with different types of cancer experienced some challenges which prevent them from living a normal life. The purpose of the study was to explore and describe the experiences of cancer patients receiving treatment at the Oshakati Oncology Clinic in Namibia. This study employed a qualitative exploratory research design to understand the experiences of these patients. A purposive sampling method was used to select the participants. A total of twelve patients diagnosed with different types of cancer were interviewed using an unstructured individual in-depth interview. Data were transcribed verbatim, and Tesch`s method was used to analyse the data. The study revealed multifaceted challenges which include physical constraints such as physical ailments, long distances to health facilities and excessive travelling. Cancer patients also faced financial and resource constraints. Even family members of cancer patients are financially affected, as children are less likely to stay in school due to financial constraints. They also experienced other challenges such as negative attitudes of health workers, poor communication and inadequate provision of information to patients. The study concluded that understanding these challenges can assist the government, private sectors, non- governmental organisations and health workers to come up with intervention strategies to support cancer patients effectively. The study recommends the need to decentralise oncology services and to provide in-service training to the health workers working with patients living with cancer.